Etiology and Antimicrobial Susceptibility of Bacerial Septic Arthritis and Osteomyelitis - N Kalantari; M Taherikalani; N Parvaneh; S Mamishi (Tehran University of Medical Sciences, 2007)
Background: To assess the distribution and resistance of the pathogens responsible for septic arthritis and osteomyelitis over a 10 years period in children admitted to Children's Medical Center Hospital, Tehran, Iran.Methods: Microbiologic and clinical presentation reports from 145 cases of septic arthritis and osteomyelitis from March 1995 to February 2005 were retrospectively reviewed. Results: Of 145 cases, 71(49%) had positive culture: 71.8%(51/71) of organisms were isolated from synovial fluid alone, 8.4%(6/71) from blood culture alone and 19.7% (14/71) from both synovial fluids and blood cultures. Staphylococcus aureus was the most common pathogen isolated, making up 60.5% of all positive cultures, followed by Klebsiella spp. (14%) and coagulase-negative staphylococci (8.4%). Thirty eight percent of S. aureus and 84% of coagulase-negative staphylococci isolates were resistant to cloxacillin. All isolates of S. aureus were susceptible to clindamycin and also, 89% were susceptible to vancomycin. Among Klebsiella spp., amikacin was shown to be very effective, with susceptibility rates of 100%. Haemophilus influenzae was identified in only 2% of all patients.Conclusion: The present study highlights the importance of characterizing the etiology and antibiotic susceptibility of organisms causing septic arthritis or osteomylitis in children.